Indians as Soldiers, 1919-1945 - Bonnie Lynn-Sherow (Symphony in the Flint Hills, 2013)
In the summer of 1918, Richard Fool Bull sent greetings in his native Lakota to the agency at Rosebud, South Dakota, from Camp Funston in Kansas. “How Cola,” he began, “I am getting to be quite a soldier learning right along.... I got a dandy rifle and bayonet and I am anxious to make use of them on some German.
Keywords: Haskell; Indians; Native Americans; army; military; combat; Camp Funston; Fort Riley; Office of Indian Affairs; drill; Rosebud boys; training; War Department; soldier; troop; World War II; Cavalry Division